SWOT Analysis for the Build up Idea of Security Pact in the Pacific - Joevi Roedyati (Current Overview on Science and Technology Research Vol. 7, 2022)
After the COVID-19 pandemic and the war between Ukraine and Russia, the world’s order has shifted, especially in light of the necessity for energy and food security. The vastly populous Chinese government has considered expanding its influence beyond its borders and has engaged in wishful thinking to prioritise its citizens. The day-to-day news in social media, mass media, government reports, and analysis of the Indo-Pacific would be included in this article. There are some main threats to security in the regional context that are identical to the catalog based on the guidelines of many contemporary security strategies: A. Possibility of the break of war, B. International terrorism existence, C. Organized crime existence Illegal immigration occurred, D. Social tensions E. Environmental disasters F. Epidemic or pandemic outbreak G. Demographic threats associated with low population growth, H. Aging population.